Nigeria’s Foreign Policy in the Post-Cold War Era: An Appraisal of Its Economic Diplomacy - Hassan , Muritala Babatunde; Adejumo, Abdul Hakeem (Kashere Journal of Politics and International Relations, 2023)
Nigeria, since independence in October 1960, has strived to achieve its foreign policy objectives through various instruments - political, economic, military, psychology and cultural. However, like many other states, diplomacy has dominated the country’s foreign policy since inception. The country’s diplomatic endeavour, since independence, has oscillated between what can be described as conservative-accommodationist diplomacy, in the immediate post-independence era to assertive-liberationist diplomacy of the post-Civil War era, to civilist-economic diplomacy of the post-Cold War era. Attempt is made in this paper to assess economic diplomacy as an instrument of Nigeria’s foreign policy with specific emphasis on the experience during the fourth republic. The paper adopts historical-descriptive approach, with heavy reliance on documentary data source, and political realism as the method and theory of analysis respectively. It is established that economic diplomacy has become a fulcrum of Nigeria’s foreign policy as successive regimes since 1999 have been refocusing foreign policy towards domestic economic development. It is concluded that, though some successes were recorded in terms of repatriation of looted funds, debt relief, and attraction of foreign investment, these are yet to translate to economic development and well-being of Nigerians. For the gains of economic diplomacy to translate to socio-economic development, it is recommended that political leadership needs to imbibe the culture of transparency and accountability in utilizing the proceeds of debt relief and repatriated funds while the necessary domestic preconditions for impactful foreign direct investment need to be guaranteed.